Spatial Data Identifying Strategic Forest Reserves that can Protect Biodiversity in the Western United States and Mitigate Climate Change - Logan T Berner; Beverly E Law; Polly C Buotte; David J Mildrexler; William J Ripple (PANGAEA, 2021)
To support local to international actions on climate change mitigation and biodiversity conservation, this spatial dataset prioritizes forestlands for preservation in the Western United States. The need for joint climate change mitigation and biodiversity conservation has led to efforts to protect 30% of land area by 2030 (30x30) and 50% by 2050 (50x50). A crucial aspects of these efforts is prioritizing lands for new protection so they best achieve climate and biodiversity goals. We developed and applied a quantitative forest preservation priority ranking (PPR) system that incorporated existing geospatial datasets related to forest carbon, biodiversity, and future vulnerabilities to climate change across the Western United States. Specifically, the forest PPR system incorporated estimates of (1) current forest carbon stocks, (2) near-term forest carbon accumulation, (3) terrestrial vertebrate species richness by taxa, (4) tree species richness, and (5) near-term forest vulnerability to increasing mortality rates from drought or fire. Input datasets were re-gridded to a common 1 x 1 km (1 km2) spatial resolution and reflect contemporary (2000-2020) and near-future (2020-2050) forest conditions, with near-future conditions derived using land surface simulations from the Community Land Model (CLM 4.5). We applied the forest PPR system such that each patch of forest (i.e., a 1 km2 grid cell) was ranked relative to others in its ecoregion based on metrics of carbon and/or biodiversity both with and without considering future vulnerabilities (i.e., six scenarios). We assessed the extent of forestlands that are currently protected (GAP 1 or 2; IUCN Ia-VI) and then identified the highest-ranked unprotected forestlands that could be preserved to meet the 30x30 and 50x50 targets using each prioritization scenario. This spatial dataset thus includes the locations of forestlands that could be strategically preserved to meet the 30x30 and 50x50 targets as prioritized using six scenarios. Each raster is provided at 1 km2 resolution in an Albers Equal Area Projection (EPSG 9822) and covers forestlands that occur across the 11 contiguous western states (i.e., Arizona, California, Colorado, Idaho, Montana, Nevada, New Mexico, Oregon, Utah, Washington, and Wyoming). Raster files are in GeoTiff format. These spatial data were produced as part of Law et al. (2021) and support cross-scale efforts to preserve forests for climate change mitigation and biodiversity conservation.